Implementation of Inside Outside Circle Method to Develop Students' Critical Thinking Skills at SMA Muhammadiyah 10 Surabaya - Hafidz, Abdul; Arifin, Shokhibul; Hidayat, Moch Charis (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Education plays an important role in the progress of a country because the improvement of human resources depends on education. Communication in science is very important because others will not know what to do or plan without it. The Inside Outside Circle (IOC) model enters the learning process and helps students become more active in class. The role of teachers is very important in achieving learning objectives. The Inside Outside Circle type of cooperative learning that uses small and large circle patterns emphasizes cooperation, discipline, independence, and critical thinking of students. This is one strategy that can be used to achieve these goals. and encourage them to actively participate in the learning process. This study is about the application of the inside outside circle learning model to improve students' critical thinking behavior in Islamic Religious Education subjects, and the subjects of this study are Islamic Religious Education teachers and all students at SMA Muhammadiyah 10 Surabaya. This study uses a qualitative method with an Ethnographic approach. This is a classroom action research with three cycles of two meetings each.And for the data collection technique I use observation, interviews, and documentation. Observation is done by observing the learning that takes place. Compared to previous studies, this study measures students' critical thinking skills and their learning outcomes by using the Inside Outside Circle learning model in Islamic religious education lessons at SMA Muhammadiyah 10 Surabaya. The Inside Outside Circle model is a learning model that utilizes real problems as a basis for students to learn and allows them to improve their ability to construct their own knowledge.